2021
DOI: 10.1111/ecc.13487
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression status prior to radiotherapy in patients with nasopharyngeal carcinoma and its effect on acute radiation toxicities

Abstract: Objective: The objective of this work is to explore anxiety and depression status prior to radiotherapy in patients with nasopharyngeal carcinoma (NPC) and its effect on acute radiation toxicities.Methods: A total of 267 NPC patients were enrolled between August 2013 and September 2016. The anxiety and depression status of the patients prior to radiotherapy was evaluated using the Hospital Anxiety and Depression Scale. Acute radiation toxicities were assessed weekly and recorded according to the Common Termino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Additionally, forecasting-based countermeasures were taken and rehabilitation training targeted at trismus was given to patients to avoid similar adverse reactions [ 27 ]; preventive measures such as rinsing the oral and nasal cavities were effective to prevent stomatitis; avoidance of exposure to the sun greatly reduced the incidence of radiodermatitis. The self-care plus forecasting nursing could inform patients about possible adverse reactions and effective countermeasures to radiation, which improved their tolerance to radiotherapy and aroused their initiative to fight disease, thus reducing the incidence of adverse reactions substantially [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, forecasting-based countermeasures were taken and rehabilitation training targeted at trismus was given to patients to avoid similar adverse reactions [ 27 ]; preventive measures such as rinsing the oral and nasal cavities were effective to prevent stomatitis; avoidance of exposure to the sun greatly reduced the incidence of radiodermatitis. The self-care plus forecasting nursing could inform patients about possible adverse reactions and effective countermeasures to radiation, which improved their tolerance to radiotherapy and aroused their initiative to fight disease, thus reducing the incidence of adverse reactions substantially [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early nutritional intervention can improve nutritional status, increase tolerance to cancer treatment, improve QoL, and prolong survival. Depression is another poor prognostic factor for elderly patients with NPC (23). Early management of depression would help patients to better tolerate the side effects of treatment.…”
Section: Assessment Of Elderly Cancer Patient With Npcmentioning
confidence: 99%
“…Several studies have indicated that patients with nasopharyngeal carcinoma (NPC) have more psychiatric symptoms and poorer mental health than the general population [ 1 ]. Li found that in a study of 267 patients with NPC, the incidence rate for anxiety and depression were 35.2% and 25.5% respectively [ 2 ], which was higher than in the general population (4.4%) [ 3 ]. McDowell revealed that in a study of 107 patients with NPC aged 32 to 81, survivors of NPC experience many physical symptoms such as depression (25%), anxiety (37%), and fatigue (28%) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%